2021
DOI: 10.1016/j.breast.2021.02.015
|View full text |Cite
|
Sign up to set email alerts
|

First- and second-line treatment strategies for hormone-receptor (HR)-positive HER2-negative metastatic breast cancer: A real-world study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 37 publications
(42 reference statements)
3
23
0
Order By: Relevance
“…Usually, patients who have endocrine resistance are not recommended to use ET for HR+ ABC by Chinese expert consensus ( 13 ). Third, compared with ET, the higher response rates and faster response associated with CT may cause clinicians to prescribe CT to patients with rapidly progressive and symptomatic disease ( 14 , 34 ). This may be attributed to the vast heterogeneity in metastatic disease characteristics among these patients and the lack of clear prognostic indicators to guide physicians in identifying which patients may benefit from CT or ET.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, patients who have endocrine resistance are not recommended to use ET for HR+ ABC by Chinese expert consensus ( 13 ). Third, compared with ET, the higher response rates and faster response associated with CT may cause clinicians to prescribe CT to patients with rapidly progressive and symptomatic disease ( 14 , 34 ). This may be attributed to the vast heterogeneity in metastatic disease characteristics among these patients and the lack of clear prognostic indicators to guide physicians in identifying which patients may benefit from CT or ET.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that 35.3% of patients with HR+/HER2-metastatic BC received ET as front-line treatment, and 17.2% of patients who had neither visceral metastasis nor progression on (neo)adjuvant ET wrongly received CT instead of ET (32). However, in Europe and America, only 25-56% of patients receive CT in the first-line metastatic setting, which is obviously different from that in China (14,(32)(33)(34). In addition, 56.53% of patients received maintenance treatment after the disease was effectively controlled by CT, and maintenance ET (58.42%) was preferred.…”
Section: Discussionmentioning
confidence: 99%
“…A real-world retrospective study, conducted by Basile et al showed that after a first-line treatment with CDK4/6i, 60% of the patients were treated with CHT and 40% with ET. Patients who received ET had a better prognosis, but the authors failed to identify any significant factor with an influence on the choice of treatment after CDK4/6i [ 49 ].…”
Section: Treatment Strategies After Cdk4/6i: What Is Known What Is On...mentioning
confidence: 99%
“…As we could expect, a worse prognosis was identified for patients treated with CHT after CDK4/6i. The authors analyzed the potential factors that could have influenced the choice of second-line treatment, but they didn’t find any that seems to drive the choice of subsequential ET or CHT [ 49 ].…”
Section: Treatment Strategies After Cdk4/6i: What Is Known What Is On...mentioning
confidence: 99%
“…These seminal studies have open the way to the testing of specific CDK4 and CDK6 small molecule inhibitors (hereafter CDK4/6i) to treat human tumors, in particular estrogen receptor positive (ER+) breast cancers, in which their use, combined with hormonal therapies, has proved highly effective in the control of disease progression [ 14 , 15 , 16 , 17 ].…”
Section: The Role Of Cdk4 and Cdk6 In The Control Of Cell Cycle Progressionmentioning
confidence: 99%